Implementation of Accelerated Learning to Improve Mathematics Communication Ability - Harisuddin, Muhammad Iqbal; Sriyanti, Ika; Wijaya, Handri (FKIP Universitas Lampung, 2022)
The four skills needed in the 21st century are often abbreviated as 4Cs, including communication skills. This research is an attempt to determine students' mathematical communication skills and student responses in learning mathematics. The purpose of this study was to determine the significant improvement in communication skills and to determine student responses to the implementation of accelerated learning. This research uses Quasi Experimental Design with Non-equivalent Control Group Design. Pretest and Posttest in the form of quantitative data in the form of description questions and non-test (questionnaire) in the form of qualitative data. The research was carried out at SMPN 4 Purwadadi with the research population in the odd semester of the 2021/2022 academic year. Sampling using purposive sampling method. The instruments used are test and non-test instruments. The test instrument for students' mathematical communication skills is in the form of description questions and nontest in the form of student response questionnaires. The results of the study by using inferential statistics with a significance level of 5% showed that there was a significant difference regarding the improvement of students' mathematical communication skills and the good response of students to the use of accelerated learning.Keywords:accelerated learning, mathematical communication, junior high school student. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1409-1422